The Effect of Television Advertisement on Buying Behavior and Loyalty of Consumer With Reference to Clinic plus Shampoo in Kathmandu Valley - Itani, Rachana (Nepalese Journal of Management, 2024)
This study examines the effect of television advertisement on buying behavior and loyalty of consumer with reference to Clinic Plus Shampoo Kathmandu Valley. Consumer buying behavior is the dependent variable. The selected independent variables are price of commodity, television advertisement, consumer awareness, brand loyalty, and user’s satisfaction. The primary source of data is used to assess the opinions of respondents regarding price of commodity, television advertisement, consumer awareness, brand loyalty, and user’s satisfaction. The study is based on primary data of 118 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the effect of television advertisement on buying behavior and loyalty of consumer with reference to Clinic plus Shampoo in Kathmandu Valley. The study showed a positive impact of price of commodity on consumer buying behavior. It indicates that affordable price of commodity leads to increase in consumer buying behavior towards clinic plus shampoo. Similarly, the study showed a positive impact of television advertisement on consumer buying behavior. It indicates that attractive television advertisement leads to increase in consumer buying behavior. Likewise, the study also revealed a positive impact of consumer awareness on consumer buying behavior. It indicates that higher consumer awareness leads to increase in consumer buying behavior. In addition, the study observed a positive impact of brand loyalty on consumer buying behavior. It indicates that brand loyalty leads to increase in consumer buying behavior. Further, the study observed a positive impact of user’s satisfaction on consumer buying behavior. It implies that higher level of satisfaction leads to increase in consumer buying behavior.